3D Printed Composite Structures for Bone Repair and Dru g Delivery Application - Macha, Innocent J.; William, Joshua C.; Mtebwa, Mahamudu H.; Mtei, Regina P. (Tanzania Journal of Engineering and Technology, 2025)
Due to the increase in traffic accidents, industrial contingencies, and natural disasters, there is a high demand for bone regeneration bio materials. Although bone can regenerate and self-repair, it is difficult to do so when the defect area exceeds the critical repair area due to trauma, tumor resection, or congenital diseases. The traditional methods for bone repair are auto graft, allograft, and xenograft. However, these methods have flaws and limitations, such as complications in the donor bone area, a limited number of donors, rejection, and infectious diseases. However, in recent years, the use of additive manufacturing technologies in bone tissue engineering has increased. Three-dimensional printing (3DP) is gaining popularity among the various technology options due to its ability to directly print porous composite with designed shape, controlled chemistry, and interconnected porosity. Some of these inorganic composites are biodegradable and have proven ideal for bone tissue engineering, with the ability to deliver growth factors or drugs to specific sites. The purpose of this study is to discuss recent advancements in 3D printed bone tissue engineering composite, as well as current challenges and future directions. Studies related to tissue engineering applications, specifically, orthopedics were emphasized. The future perspectives and possible research areas have been potentially proposed